1961
DOI: 10.1128/jb.82.6.984-993.1961
|View full text |Cite
|
Sign up to set email alerts
|

Lysogeny in Staphylococci

Abstract: Changes in the phage typing patterns of strains of staphylococci of the 80/81-52/52A/80/ 81 complex and of phage group III were produced by lysogenization with temperate phages derived from selected strains of Staphylococcus aureus. The phages used were of the serological groups A, B, and F. Certain changes of phage pattern were related to serologically specific prophage immunity; others were nonspecific, or resulted from the conversion of a strain from partial resistance to full sensitivity to certain typing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1963
1963
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Similarly, a change from streptomycin sensitivity to resistance by lysogeny of a sensitive strain is described by Cavallo and Terranova (1955). Blair and Carr (1961) also found that it was possible to confer the ability to produce N hemolysin on nontoxigenic strains by lysogenization with a phage obtained from a toxigenic strain.…”
Section: Staphylococcus Aureus Rosenbachmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, a change from streptomycin sensitivity to resistance by lysogeny of a sensitive strain is described by Cavallo and Terranova (1955). Blair and Carr (1961) also found that it was possible to confer the ability to produce N hemolysin on nontoxigenic strains by lysogenization with a phage obtained from a toxigenic strain.…”
Section: Staphylococcus Aureus Rosenbachmentioning
confidence: 98%
“…The observed correlations between phage type, antigenic structure, antibiotic pattern, and enzymatic composition could be caused by the influence of the prophage on the cell nucleus. Some evidence for this is provided by the results of Blair and Carr (1961), who showed that it was possible to make a strain resistant to penicillin and at the same time change its phage typing pattern by lysogenization with appropriate phages. Similarly, a change from streptomycin sensitivity to resistance by lysogeny of a sensitive strain is described by Cavallo and Terranova (1955).…”
Section: Staphylococcus Aureus Rosenbachmentioning
confidence: 99%
“…In addition, as a ubiquitous opportunistic pathogen and metabolically versatile species, there were several incentives for understanding genetic exchange in P. aeruginosa. Numerous other bacteria that occasionally inhabit freshwater such as Escherichia coli, (Migula 1985) Castellani and Chalmers 1919, and Staphylococcus aureus (Rosenbach 1884), Vibrio mimicus (Davis et al 1982), V. cholera (Pacini 1854), Proteus species and Corynebacterium diphtheria (Kruse 1886) Lehmann and Neuman 1896, have been used as model species to study the phenomenon of lysogenic conversion where phage genomes containing genes linked to host pathogenicity transmit these genes through infection (Groman, 1955;Blair & Carr, 1961;Coetzee, 1961;De Waart, Winkler & Grootsen, 1962;Waldor & Mekalanos, 1996;Karaolis et al, 1999;Boyd et al, 2000;Campos et al, 2003;Davis & Waldor, 2003). However, none of these seminal studies has been followed up with investigations in freshwaters to fully understand the environmental conditions that support the establishment of lysogeny and the ecological advantages of lysogenic conversion in the context of transduction.…”
Section: Introductionmentioning
confidence: 99%
“…numerous other bacterial species which contain both toxic and nontoxic strains. For example, both toxic and nontoxic strains have been reported for Corynebacterium diphtheriae (4,11,12), Streptococcus pyogenes (23,43), Staphylococcus aureus (5,41,42), and Clostridium botulinum (16,19,20,22).…”
mentioning
confidence: 99%